From Great Leaders to Great Employees: The Impact of Transformational Leadership and Organizational Commitment on OCB through Job Satisfaction - Sarwanto, Joko Tri; Wiwoho, Gunarso (Journal of Educational Management Research, 2025)
The level of OCB among teachers tends to vary, even though every institution expects all teachers to exhibit high OCB. This study aims to analyze the influence of transformational leadership and organizational commitment on Organizational Citizenship Behavior (OCB), both directly and through the mediation of job satisfaction. The independent variables in this study are transformational leadership and organizational commitment. Job satisfaction acts as the mediating variable, while OCB is the dependent variable. All teachers were included as respondents using a saturated sampling technique. Data were collected through questionnaires and analyzed using the Structural Equation Modeling (SEM) method with Smart PLS 4.0. The results show that transformational leadership has no significant effect on OCB, while organizational commitment has a significant effect on OCB. Furthermore, both transformational leadership and organizational commitment have a significant effect on job satisfaction. Job satisfaction also has a significant effect on OCB. In this case, job satisfaction is proven to be able to mediate the influence of transformational leadership and organizational commitment on OCB.